ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 PADA PT. HASJRAT MULTIFINANCE, MANADO - Rampengan, Rachel Romilda; Saerang, David Paul Elia; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Income Tax Article 23 ( article 23 ) , set cutting taxes imposed on income taxpayer in the country or Permanent Establishment (PE ) derived from the capital , the delivery of services , or implementation of activities other than those of Article 21 Income Tax withheld.This study aims to determine the calculation as well as the accounting treatment of income tax article 23 and to know the tax reporting has been carried out by PT . Hasjrat Multifinance , Manado whether in accordance with applicable regulations . Object of this study was taken at. Hasjrat Multifinance , Manado using qualitative descriptive analysis method . From the results of this study concluded that PT . Hasjrat Multifinance , Manado has done the calculation and reporting of article 23 are right that is in accordance with the provisions . To deposit no later than the 10th of the next month while reporting not later than 20 days after the tax period ends .